THE EFFECT OF SOAKING IN RED GINGER ON THE QUALITY OF FRESH MUSSEL DURING STORAGE AT ROOM TEMPERATURE - Octavianus Samosir; Tjipto Leksono; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis study aims to determine the effect of immersion in red ginger on the quality of fresh mussel seen from the organoleptic values, Total Plate Count (TPC), Coliform bacteria and Escherichia coli, and to determine the best concentration of red ginger solution that is able to maintain fresh mussel quality. The method used in this study is the experimental method of immersing the mussel in red ginger and placed at room temperature. The design used in this study was a randomized block design (RBD) with 4 treatments of concentrations of red ginger 0% (K0), 50% (K1), 70% (K2), 90% (K3) and storage time 0, 3, 6 and 9 hours. Based on the results of the research that has been done, the organoleptic value and total plate number of mussels soaked in red ginger with concentrations of 50, 70 and 90% have values that are not significantly different. However, it can be concluded that red ginger with a concentration of 70% is the best treatment with a value of 8.20; aroma 8.18; texture 7.48; taste 7.78; total plate counts of 6.6x105 and negative Escherichia coli.Keywords: Mussel, Red Ginger, Organoleptic, Total Plate Count, Escherichia coli